Slice coherence in a query-based architecture for 3D heterogeneous printing. (June 2016) - Yaman, Ulas; Butt, Nabeel; Sacks, Elisha; Hoffmann, Christoph
Abstract: We report on 3D printing of artifacts with a structured, inhomogeneous interior. The interior is decomposed into cells defined by a 3D Voronoi diagram and their sites. When printing such objects, most slices the printer deposits are topologically the same and change only locally in the interior. The slicing algorithm capitalizes on this coherence and minimizes print head moves that do not deposit material. This approach has been implemented on a client/server architecture that computes the slices on the geometry side. The slices are printed by fused deposition, and are communicated upon demand. Graphical abstract: Highlights: We explore 3D Voronoi-based heterogeneous printing. We utilize Euler loops to minimize non-extruding fast travels. The motion paths of consecutive slices are almost the same. The motion paths are not generated from scratch at every slice. Only 3 local cases can arise when updating the motion paths.